2022
DOI: 10.32615/ps.2022.032
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic mechanism of high yield under an improved wide-narrow row planting pattern in maize

Abstract: Abbreviations: Ci -intercellular CO2 concentration; E -transpiration rate; gs -stomatal conductance; LI -light interception of the stand; LMA -leaf mass per unit area; LUE -light-use efficiency; MDH -malate dehydrogenase; ME -malic enzyme; N area -nitrogen content per unit area; PEPC -phosphoenolpyruvate carboxylase; PN -net photosynthetic rate; PNUE -photosynthetic nitrogen-use efficiency; PPDK -pyruvate orthophosphate dikinase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Similarly, Grevenitios et al [27] found a higher yield of 1.0 t ha −1 in narrow rows. A difference of 1.2 and 1.8 t ha −1 in favor of narrow rows was found by Testa et al [29] and Ge et al [30], respectively. No interaction of row spacing × plant density was found in any of these studies.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Similarly, Grevenitios et al [27] found a higher yield of 1.0 t ha −1 in narrow rows. A difference of 1.2 and 1.8 t ha −1 in favor of narrow rows was found by Testa et al [29] and Ge et al [30], respectively. No interaction of row spacing × plant density was found in any of these studies.…”
Section: Introductionmentioning
confidence: 70%
“…The differences in maize yield potential and actual yields point to further possible yield increases due to advances in plant breeding and improved agronomic practices [37]. Experiments with alternative spatial arrangement have been conducted predominantly in North and South America [24,32,38,39] or Asia [18,30,34,35]; however, there is a lack of studies in Central Europe where wide rows are standard and other spatial arrangements are rarely used. The growing season significantly impacts maize yield [9,27], and, therefore, the effect of row spacing needs to be evaluated in experiments over several years.…”
Section: Introductionmentioning
confidence: 99%